2012
DOI: 10.4236/ojpm.2012.24071
|View full text |Cite
|
Sign up to set email alerts
|

Mode of travel and the decision to allow children to walk or bike to schools—The Abu Dhabi experience

Abstract: The study investigates school travel to and from schools as perceived by parents in Abu Dhabi, United Arab Emirates. Far fewer children are cycling or walking to school, and more and more are being driven to school by car. Traffic conditions, environmental factors, distance to school, road's infrastructures, walking or biking with groups, schools efforts to educate children about active travel, and preferences of parents to accompany children to school were significantly perceived as important. The absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
(137 reference statements)
0
5
0
Order By: Relevance
“…In a study investigating travel to school, in Abu Dhabi, UAE, far fewer children are cycling or walking to school. On the contrary, the majority are being driven to school by car [20]. Absence of active travel culture in the community is seen as a significant contributory factor.…”
Section: Discussionmentioning
confidence: 99%
“…In a study investigating travel to school, in Abu Dhabi, UAE, far fewer children are cycling or walking to school. On the contrary, the majority are being driven to school by car [20]. Absence of active travel culture in the community is seen as a significant contributory factor.…”
Section: Discussionmentioning
confidence: 99%
“…Various environmental/culturalissueshave contributed to reduced children activity. In a study investigating travel to school, in Abu Dhabi, it was found that children in the UAE are increasingly using cars for their short travels compared to earlier periods of time and far fewer children are cycling or walking to school [22]. Absence of active travel culture in the community is seen as a significant contributory factor.…”
Section: Discussionmentioning
confidence: 99%
“…In Abu Dhabi, the main concern is over the policies surrounding the built environment that make it hard to walk to school [41]. ADEK and ADPM may adopt transformative strategic options to promote active commuting to school as the primary mode of transportation.…”
Section: Implications For Built Environmentmentioning
confidence: 99%